1994
DOI: 10.1111/j.1365-2125.1994.tb04232.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of some factors responsible for a food‐induced increase in absorption of atovaquone.

Abstract: 1. Atovaquone is a potent antiprotozoal slowly and irregularly absorbed after administration as tablets to fasting volunteers. A series of studies was performed to investigate the effects of food, bile and formulation on atovaquone absorption. 2. In 18 healthy male volunteers, a high‐fat breakfast administered 45 min before 500 mg atovaquone as tablets increased AUC by 3.3‐fold (95% CI 2.8‐4.0) and Cmax 5.3‐fold (4.3‐6.6) compared with fasting. 3. The absorption of atovaquone from tablets was examined in 12 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 19 publications
(30 reference statements)
1
58
1
3
Order By: Relevance
“…As a control, pulverised atovaquone was homogeneously dispersed in an aqueous solution of methylcellulose. The resulting suspension showed a mean particle diameter of about 640 nm, which was smaller than particle sizes previously reported by other research groups (Rolan et al 1994;Dearn 2000;Dixon et al 1996).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…As a control, pulverised atovaquone was homogeneously dispersed in an aqueous solution of methylcellulose. The resulting suspension showed a mean particle diameter of about 640 nm, which was smaller than particle sizes previously reported by other research groups (Rolan et al 1994;Dearn 2000;Dixon et al 1996).…”
Section: Discussioncontrasting
confidence: 59%
“…Thus, it was demonstrated that, for both the tablet and suspension formulations, the atovaquone concentration in plasma is greater when the drug is administered with food (Rolan et al 1994;Dixon et al 1996). Overall, it has been calculated that food increases the bioavailability of atovaquone 1.4-fold over that achieved in a fasting state (Rolan et al 1994); although, this amount can be higher depending on the fat content of the meal (Nicolaides et al 1999). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the ingestion of food increases the bioavailability of atovaquone 17 and consequently all treatment regimens were administered within 45 min of a small meal. Medication was taken under direct supervision of trained field workers and compliance was further confirmed by a tablet count.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Drug-food, drug-drug and drug-herb interactions are factors that can alter the pharmacokinetic activity of a drug; these interactions can occur during absorption, distribution, metabolism or excretion. 7 Catha edulis of the Celastraceae family, also known as khat, is a plant widely cultivated in East Africa (e.g.…”
mentioning
confidence: 99%